The Effect of Accessibility and Retail Service Quality on Repeat Purchase in the Traditional Store of the Consumer - Thitikarn Sirican; Wangbenmad, Chutima (AMAR (Andalas Management Review), 2025)
This study aimed to examine the influence of accessibility and retail service quality of traditional retail stores on consumers’ repeat purchase decisions. The sample consisted of 400 consumers who had made repeat purchases from traditional retail stores in the Su-ngai Kolok District, Narathiwat Province. Data were analyzed using descriptive statistics (percentage, mean, and standard deviation) and inferential statistics, specifically stepwise multiple regression analysis. The quantitative findings revealed that consumers perceived a high level of accessibility to traditional retail stores, which included: (1) proximity of the store to their residence, (2) ease of travel, (3) short travel time, and (4) low transportation costs. Additionally, retail service quality was rated at a high level across several dimensions: physical aspects, reliability, interpersonal interaction, problem-solving, and store policies. The regression analysis indicated that four factors—accessibility, interpersonal interaction, store policies, and physical aspects—could jointly predict 61.9% of the variance in consumers’ repeat purchase decisions.